2010
DOI: 10.1890/090015
|View full text |Cite
|
Sign up to set email alerts
|

An alternative approach for quantifying climate regulation by ecosystems

Abstract: Ecosystems provide multiple benefits to people, including climate regulation. Previous efforts to quantify this ecosystem service have been either largely conceptual or based on complex atmospheric models. Here, we review previous research on this topic and propose a new and simple analytical approach for estimating the physical regulation of climate by ecosystems. The proposed metric estimates how land‐cover change affects the loading of heat and moisture into the atmosphere, while also accounting for the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 44 publications
3
73
0
1
Order By: Relevance
“…Indeed, other studies have shown that tropical deforestation increases mean global surface temperature, whereas deforestation in temperate and boreal regions has, if anything, a net cooling effect 1,22 . This highlights the critical importance of tropical forests for climate protection 1,2,6,21 , supporting the argument that efforts to mitigate climate change through avoided deforestation or afforestation efforts (for example, REDD+; ref. 3) will be most effective if focused on tropical forests 2,10,13 .…”
Section: Letters Nature Climate Change Doi: 101038/nclimate1346supporting
confidence: 54%
See 1 more Smart Citation
“…Indeed, other studies have shown that tropical deforestation increases mean global surface temperature, whereas deforestation in temperate and boreal regions has, if anything, a net cooling effect 1,22 . This highlights the critical importance of tropical forests for climate protection 1,2,6,21 , supporting the argument that efforts to mitigate climate change through avoided deforestation or afforestation efforts (for example, REDD+; ref. 3) will be most effective if focused on tropical forests 2,10,13 .…”
Section: Letters Nature Climate Change Doi: 101038/nclimate1346supporting
confidence: 54%
“…Terrestrial ecosystems also strongly affect climate through their control over albedo and evapotransipiration 5,6,8,16,21,22 . Vegetated surfaces-especially forests-typically have lower albedos than bare ground and therefore absorb more incoming solar radiation.…”
mentioning
confidence: 99%
“…Ecosystem services affected by agriculture include provisioning of food, fiber, and freshwater, regulation of climate through carbon storage as well as biophysical influence on regional air temperature and moisture, regulation of soil and groundwater recharge, runoff, and nutrient flows to freshwater, and cultural values of landscapes (2,11,23,34,36,37). In addition, agriculture directly affects aspects of natural capital like heterogeneity of landscapes, which includes diversity of ecosystem types and species (12,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Cultivation of forest vegetation has more pronounced effects on the local climate than sparse vegetation (Fig. 4) because forested areas generally have a lower albedo, higher vegetative cover and leaf area index, and higher maximum transpiration rates than most shrub and grass ecosystems (Bonan, 2002;West et al, 2011). The total atmospheric carbon involved in the photosynthesis by shrubs to generate the same formula unit of oxygen was the most, as living organisms depend on chlorophyll content for the conversion of light energy into chemical free energy (Gest, 1993).…”
Section: Effects Of Gfgp On Ecosystem Servicesmentioning
confidence: 99%